Analytical model for high-velocity perforation of moderately thick ultra-high molecular weight polyethylene-woven laminated plates. (July 2015) - Chen, Changhai; Zhu, Xi; Hou, Hailiang; Luo, Zhong; Tang, Ting
An analytical model is developed for high-velocity perforation of moderately thick, plain-woven laminated plates by deformable blunt projectiles. Based on different mechanical states and energy-dissipative mechanisms, penetration is divided into three consecutive stages: cratering and mushrooming, shearing and compression, and stretching deformation. The model is based on the concept of energy conservation, which allows approximative calculation of residual velocity, and hence, ballistic limit. The model is validated by using experimental results for ultra-high molecular weight polyethylene-woven laminated plates in terms of residual velocity and ballistic limit. The model considers the mushrooming deformation of projectiles. Consequently, as projectile velocity increases, the accuracy and universality of the model improve.